Care management in coping with COVID-19 at a teaching hospital - Elizabeth Bernardino; Jaqueline Dias do Nascimento; Sonia Mara Raboni; Solange Meira de Sousa (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to report the experience of implementing care management strategies in coping with the COVID-19 pandemic in a teaching hospital. Method: this is an experience report of the managers who work at the largest public hospital in Paraná with functions as Head of the Care Management Division, Head of the Care Lines Management Sector, Head of the Infectiology Unit and support team. Results: care management strategies were structured based on the service dynamics; physical structure; human Resources; professional and user safety. Final considerations: preparing for a pandemic involves measures that include modifying infrastructure and processes, managing employees and users, infection prevention strategies, and clinical recommendations. These measures are necessary to optimize the quality of care provided to users with COVID-19 and to reduce the risk of viral transmission to other users or health professionals.